Foreign Bodies in Ear, Nose and Throat: An Experience from a Tertiary Care Hospital in Central Nepal - Pokharel, Apar (Nepal Medical College Journal, 2019)
Foreign bodies are frequently encountered otorhinolaryngology emergency. The objective of this research paper is to analyze different foreign bodies in terms of type, site, age, and gender distribution and methods of removal. A retrospective study was performed from March, 2018 to March, 2019 in a tertiary care hospital in the central part of Nepal. The information was obtained from hospital record books. A total of 315 patients visited the hospital with a foreign body in either of their ear, nose or throat. It comprised of approximately 12% of all the ENT emergencies in the hospital in the last one year of study. Foreign bodies in ear, nose and throat region were found in all age groups, although it was more prevalent among children of age group less than 10 years.